The gilded years : a novel - Tanabe, Karin (Washington Square Press, 2016)
"Since childhood, Anita Hemmings has longed to attend the country's most exclusive school for women, Vassar College. Now, a bright, beautiful senior in the class of 1897, she is hiding a secret that would have banned her from admission: Anita is the only African-American student ever to attend Vassar. With her olive complexion and dark hair, this daughter of a janitor and descendant of slaves has successfully passed as white, but now finds herself rooming with Louise "Lottie" Taylor, the scion of one of New York's most prominent families. Though Anita has kept herself at a distance from her classmates, Lottie's sphere of influence is inescapable, her energy irresistible, and the two become fast friends. Pulled into her elite world, Anita learns what it's like to be treated as a wealthy, educated white woman--the person everyone believes her to be--and even finds herself in a heady romance with a moneyed Harvard student. It's only when Lottie becomes infatuated with Anita's brother, Frederick, whose skin is almost as light as his sister's, that the situation becomes particularly perilous. And as Anita's college graduation looms, those closest to her will be the ones to dangerously threaten her secret. Set against the vibrant backdrop of the Gilded Age, an era when old money traditions collided with modern ideas, Tanabe has written an unputdownable and emotionally compelling story of hope, sacrifice, and betrayal--and a gripping account of how one woman dared to risk everything for the chance at a better life"--